2020
DOI: 10.1186/s10086-020-01864-5
|View full text |Cite
|
Sign up to set email alerts
|

Detection and visualization of encoded local features as anatomical predictors in cross-sectional images of Lauraceae

Abstract: This paper describes computer vision-based quantitative microscopy and its application toward better understanding species specificity. An image dataset of the Lauraceae family that consists of nine species across six genera was investigated, and structural features were quantified using encoded local features implemented in a bag-of-features framework. Of the algorithms used for feature detection, the scale-invariant feature transform (SIFT) achieved the best performance in species discrimination. In the bag-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 16 publications
0
19
0
Order By: Relevance
“…The superiority of SIFT has been demonstrated in comparative studies of major local feature extraction algorithms in general image classification [18]. For wood identification, it has been reported that SIFT, which actively detects cell corners, is superior to other local feature algorithms [4]. As parameters of the SIFT algorithm for feature extraction, the number of layers in each octave was set to 3, the contrast and edge thresholds were set to 0.06 and 10, respectively, and the sigma value of the Gaussian applied to the image at octave number 0 was set to 1.6.…”
Section: Feature Extraction and Encodingmentioning
confidence: 99%
See 4 more Smart Citations
“…The superiority of SIFT has been demonstrated in comparative studies of major local feature extraction algorithms in general image classification [18]. For wood identification, it has been reported that SIFT, which actively detects cell corners, is superior to other local feature algorithms [4]. As parameters of the SIFT algorithm for feature extraction, the number of layers in each octave was set to 3, the contrast and edge thresholds were set to 0.06 and 10, respectively, and the sigma value of the Gaussian applied to the image at octave number 0 was set to 1.6.…”
Section: Feature Extraction and Encodingmentioning
confidence: 99%
“…Because the XDD_005 dataset has quite imbalanced classes, the F1 score was used as a metric to evaluate the performance of the established models. The F1 score is the harmonic mean of the precision and recall, and is more appropriate than the accuracy for evaluating models that have been trained using an imbalanced dataset [4].…”
Section: Data Learning and Performance Metricmentioning
confidence: 99%
See 3 more Smart Citations